2009
DOI: 10.1007/s00208-009-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

Locally conformal Kähler manifolds with potential

Abstract: A locally conformally Kähler (LCK) manifold M is one which is covered by a Kähler manifold M with the deck transformation group acting conformally on M. If M admits a holomorphic flow, acting on M conformally, it is called a Vaisman manifold. Neither the class of LCK manifolds nor that of Vaisman manifolds is stable under small deformations. We define a new class of LCK-manifolds, called LCK manifolds with potential, which is closed under small deformations. All Vaisman manifolds are LCK with potential. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
119
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 20 publications
1
119
0
Order By: Relevance
“…It is known ( [GO], [Ve2]) that all diagonal Hopf manifolds are Vaisman. In [OV2], we have shown that any Vaisman manifold admits a holomorphic immersion into a diagonal Hopf manifold, and in [OV3] we proved that for dim C M 3 there exists an embedding into a diagonal Hopf manifold. In fact, the assumption dim C M 3 is not needed, because in [Be], all 2-dimensional Vaisman manifolds were classified, and embeddability of those into H A can be easily checked using the same arguments as in [OV3].…”
Section: Potentials On Coverings Of Lck-manifoldsmentioning
confidence: 82%
See 2 more Smart Citations
“…It is known ( [GO], [Ve2]) that all diagonal Hopf manifolds are Vaisman. In [OV2], we have shown that any Vaisman manifold admits a holomorphic immersion into a diagonal Hopf manifold, and in [OV3] we proved that for dim C M 3 there exists an embedding into a diagonal Hopf manifold. In fact, the assumption dim C M 3 is not needed, because in [Be], all 2-dimensional Vaisman manifolds were classified, and embeddability of those into H A can be easily checked using the same arguments as in [OV3].…”
Section: Potentials On Coverings Of Lck-manifoldsmentioning
confidence: 82%
“…[OV3]) to the deck group being isomorphic to Z (a condition satisfied by compact Vaisman manifolds).…”
Section: Lck Manifolds With Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…by the Hodge decomposition theorem of El Kacimi Alaoui (see Theorem 6.7), the proof is done by (38) and (42). by the complex conjugation.…”
Section: It Is Well Known Thatmentioning
confidence: 99%
“…Belgun [5] showed that both of structures are not stable under small deformations of complex structures. Note that Ornea and Verbitsky [38] discovered the stability of another class of geometric structure under small deformations of complex structures, which they call locally conformal Kähler manifolds with potential. Theorem 1.1.…”
mentioning
confidence: 99%